A memory-bounded, deterministic and terminating semantics for the synchronous programming language Céu - Lima, Guilherme F.; Santos, Rodrigo C.M.; Ierusalimschy, Roberto; Haeusler, Edward H.; Sant’Anna, Francisco (Journal of systems architecture, 2019)
Céu is a synchronous programming language for embedded soft real-time systems. It focuses on control-flow safety features in the presence of shared-memory concurrency and abortion of lines of execution, while enforcing memory-bounded, deterministic, and terminating reactions to the environment. In this work, we present a small-step structural operational semantics for Céu and prove that reactions have the properties enumerated above: that for a given arbitrary timeline of input events, multiple executions of the same program always react in bounded time and arrive at the same final finite memory state.